STRATEGI KOMUNIKASI MAHASISWA BAHASA JERMAN FAKULTAS SASTRA UM PADA MATAKULIAH KONVERSATION - Sri Prameswari Indriwardhani (Fakultas Sastra Universitas Negeri Malang, 2012)
The Communication Strategy is a systematic technique used by foreign language learners to express their ideas when they have difficulties to communicate due to their incomplete mastery of B2. Konversation course is a subject in which the students are to speak freely with a particular topic; moreover, the learners have been equipped with simple linguistic rules, so that they have a tendency to seek ways to make the message acceptable. Communication strategy that is widely used by JSJ UM students are transfers, because not only they literally translate concepts but they also use terms and vocabulary from their mother tongue and English in uttering German. The reasons that influence the use of these forms of communication strategy are the students’ insufficiency in mastering grammar and vocabulary skills to be able to communicate in a variety of fields because they are still at the early stages of learning.